THE ROLE OF A NEW BIOMARKER GROWTH DIFFERENTIATION FACTOR 15 IN PROGNOSIS OF PATIENTS WITH ACUTE CORONARY SYNDROME AND TYPE 2 DIABETES MELLITUS - Kopytsya, M. P.; Petyunina, O. V.; Vyshnevska, I. R.; Tytarenko, N. V.; Hilova, Y. V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Numerous studies confirm worse results in diabetic patients with acute coronary syndrome (ACS) compared with non-diabetic patients. Different mechanisms underlie the adverse outcomes of ACS and diabetes mellitus. In this connection, a special place is occupied by the study of new biomarkers that reflect the complex pathogenic processes in these patients. Purpose: to investigate the role of the biomarker GDF 15 in prognosis of adverse outcomes in type 2 diabetes mellitus (DM2T) patients with ACS. Materials and methods: 73 patients with different forms of ACS were screened. Levels of biomarkers: GDF 15, N-terminal pro brain natriuretic peptide (NT-pro BNP) and C-reactive protein (C-RP) were determined. The follow up period was 1 year. Endpoint was defined as lethal outcome. Results: significant differences in GDF 15 level has been found, prognostic value of GDF 15 was estimated in patients with DM2T, using a ROC-analysis. Threshold level of GDF 15 has been determined as 3894 pg/ml, with sensitivity of 64 % and specificity of 75 %. Conclusion: Patients with ACS and DM2T more often had a history of different cardiovascular diseases and risk factors compared to patients without diabetes. GDF 15 level was significantly higher in patients with ACS who had history of DM2T.